The relationship between the role of the spirit of God and the growth of the church - Georges Nicolas Djone (STABN RADEN WIJAYA WONOGIRI, 2022)
This paper aims to analyze the relationship between the role of the Spirit of God and the growth of the Church by using a qualitative descriptive method related to the experience of the early Church. Today, some churches are led and managed like a company based on worldly principles by ignoring the vital role of the Holy Spirit in them. Data collection was carried out through the Bible, journal literature, and books, as well as interviews. The result: First, through His role, the Spirit of God equips and prepares believers in the context of carrying out ministry duties. Second, through His part, the Spirit of God in cooperating with believers produces church growth in all aspects. In conclusion, the relationship between the role of God's Spirit and church growth is to equip and prepare believers to carry out their ministry duties according to their calling and to work with them to produce church growth according to God's plan.